The Implementation of Suggestopedia Method in Arabic Teaching for Qirā’ah - Yogia Prihartini; Wahyudi Buska; Nur Hasnah Nur Hasnah (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2019)
This research is meant to find that qirā’ah is one of important factors to see Arabic achievement as well as istimā’, kalām and kitābah. Other factors are from the methods of teaching like: TPR (Total Physical Response), Silent way, and Community Language Learning and suggestopedia method. In this paper the writer limits the problem by focusing on teaching qirā’ah descriptive paragraph through suggestopedia method. The writer formulates the problem of this paper. The formulation is